Communication as a Tool in Policy Reform : Getting the Message Through in Egypt - Moullier, Thomas (World Bank, Washington, DC, 2012)
At the end of 2005, the recently appointed reformist government led by Prime Minister Ahmed Nazif started to engage in drastic reforms of the business environment. Building on the momentum created by a successful tax reform, the government, through the General Authority for Free Zones and Investment (GAFI), took a very active role in the establishment of one-stop-shop facilities. But despite some visible progress, GAFI was still baffled by the difficulty of re-engineering administrative processes and achieving an effective delegation of authority from central line ministries to their local authorities. One obvious constraint faced by GAFI in Alexandria was the limited knowledge and understanding of the reform process by Egypt's civil servants. Equally, GAFI suffered from a lack of effective recognition and support from the private sector for the government's genuine commitment to turn Egypt into a more transparent and predictable place for start-up investors.